Generation of 3D Coverage Map - Erbas, Ugur; Tabakcioglu, Mehmet Baris (Ieee, 2022)
With the developing communication technology in recent years, the importance of placing the base stations in the right location has increased in order to ensure a healthy communication. It is thought that this situation will become even more important with 5G technology. In this study, 2D maps with earth maps and transformation windows were created in MATLAB using 3D digital data. The diffracted, direct and reflected rays were determined, and the ray tracing algorithm was run for the superconducting surface. A 3D coverage area is mapped for a possible transmitter position. Electric field graphs are drawn for different heights. It has been observed that the electric field graph changes depending on the landforms, distance, diffraction and interference of the rays.
30th IEEE Signal Processing and Communications Applications Conference (SIU) -- MAY 15-18, 2022 -- Safranbolu, TURKEY
Keywords: Caverage map; Geometric Optic; Uniform Theory of Diffraction; Ray tracing; Base station placement